Keunggulan Kolaborasi Media Pembelajaran Manual Versus Digital sebagai Upaya Meningkatkan Kemampuan Berhitung Siswa pada Materi Bilangan Bulat Tingkat Sekolah Dasar - Triana Nur Lailiya; Nisrina Dania Salsabila; Dawia Salsabila; Iesyah Rodliyah (Discovery, 2026)
This research is motivated by the low ability of students in arithmetic, especially in whole number material, so that there are still many students who get learning outcomes that do not meet the minimum completeness criteria. The aim of this research is to describe the effectiveness of manual versus digital learning media collaboration on learning outcomes and student responses. The research design used was a pre-experimental design with a One-Shot Case Study design. The One-Shot Case Study research design is research that collects data from one group that is given treatment, then carries out a posttest, and a response questionnaire is given. The posttest results were analyzed based on the minimum regulatory criteria (KKM). Based on the results of data analysis, classical student learning outcomes show that 80% of students have met the minimum completeness criteria. Meanwhile, the results of the student response questionnaire also showed a positive response with a score of 91%. This means that the collaboration between manual versus digital learning media is effective because it is able to improve student learning outcomes and is able to provide positive responses to students.